ANALISIS YURIDIS PEMBEBANAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN PADA PEWARISAN BAGI TANAH BERSERTIFIKAT DAN TANAH YANG BELUM BERSERTIFIKAT (Studi Kasus di Kabupaten Sleman) - , CLAUDYA M. NOVIATY TEKU WIO, Prof. Dr. Sudjito, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Rights switchover because of endowment happened by that law at the time of handle of rights or heir pass away, after the date of that all heir become the new rights handle, concerning whosoever becoming heir set by law going into effect to all heir. This matter not miss from payment of Iease BPHTB which is obliged to be done by heir in the event of tax payable BPHTB. Research about encumbering of toll of acquirement of land right and building at endowment for land of have certificate and for land which not yet certificate in Sleman Regency aim to to know and comprehend the process of encumbering BPHTB that happened because endowment of land of have certificate and for land which not yet have certificate in Sleman Regency and know the cause happened by the difference of imposition BPHTB at endowment of land of have certificate and land not yet have certificate. This research use the approach method by yuridic empirical, that is use the explanatory law norm by checking and studying regulation applicable law in this time to registration of rights switchover because of endowment and its Iease BPHTB encumbering and its execution through field research to get the primary data. Pursuant to result of research shows that: first, in execution process the endowment of land of have certificate and land not yet have certificate, all heir beforehand ask the bank statement heir, and letter which deal with endowment. In the case of process of Iease payment which its system pursuant to self assisment taxpayer given a break to count and pay by self tax payable prescribed by the regulations. Second, Because of the happening of difference of imposition of Iease BPHTB at endowment of land of have certificate and land which certificate not yet relate to the agreement all heir to divide the heritage. Land not yet have certificate, process to descend the heir at one blow convert the rights, so that contained in certificate is name of handle of rights and imposition BPHTB happened once. Land have Certificate happened by the encumbering BPHTB twice if this matter relate to the ownership of rights with ( cumulative) again become the individual rights.